Sulfur stable isotope signatures of the Morro da Pedra Preta Formation, Serra do Itaberaba Group, São Paulo State, Brazil - Garda, Gianna; Beljavskis, Paulo; Juliani, Caetano; Boyce, Adrian (Geochimica Brasiliensis, 2017)
The Serra do Itaberaba Group (Selo Paulo - Brazil) was explored in the XVIII century fur gold. Sulfur stable isotope data helped constrain four sulfidation stages that effected the basal, Morro da Pedra Preta Formation meta volcanic-sedim sequence. Syn-sedimentary pyrrhotite from Stage I (-5.47 per mil < 614S < —8.7 per mil) and Stage II (+4.48 per mil < (5’ < +7.36 per mil) sulfides resulted respectively from bacterial and thermochemical reduction of seawater sulfate. The 5-°S values obtainedfOr both. stages also reveal an igneous sulfur component, derived either from the volcanic pile being leached by hydrothermal fluids, or intruding andesite and dacite bodies that powered seawater circulation through the sequence. Free gold is associated with chalcocite and covellite after Stage III chalcopyrite (+3.6 per mil < 834S < +2.6 per mil). Pyrite predominates in Stage IV (+2.4 per mil < 8,45 < +29 per mil). Lower-temperature, submicroscopic galena (.5"S " + .1 per mil), Ag-bearing Bi tellurides and REE minerals fill cavities and fractures in sulfides of previous stages. Molybdenite (5’S °+3 per mil) and scheelite are associated with stages III and IV and related to late fluids derived from nearby Neoproterozoic granite bodies. The influence of meteoric water is not ruled out at stages III and IV, once post-magmatic fluids circulated along fault and fracture systems that crosscut the Morro da Pedra Preta Formation.